Histological findings in duodenal diseases Histologische befunde bei Dünndarmerkrankungen - Vieth, M.; Oberhuber, G.; Neumann, Helmut (Verdauungskrankheiten, 2013)
Duodenal biposies are a pre requisite for a complete endoscopy of the upper gastrointestinal tract. This is also true for cases without endoscopically visible or minor changes, only. Not performing duodenal biopsies routinely leads to the possibility that relevant diseases will not be diagnosed in time. Even the fact that relevant duodenal diseases are to be expected in much less than 10% of the cases and are rare is irrelevant since it may be very crucial to clarify symptoms that may reach from minor impairment of wellbeing to life threatening diseases. Therefore, it is important to know what to be expected from the results of duodenal biopsies. The following work was written to give a compact glance for daily routine practice. The manuscript is not designed to fulfill all needs in depth since such a format would exceed the given frame. © 2013 Dustri-Verlag Dr. Karl Feistle.
CRIS-Team Scopus Importer:2025-03-05
Keywords: Diagnosis; Disease; Endoscopy; Histology; Small bowel